Menerapkan Lesson Study Sebagai Upaya Meningkatkan Proses dan Hasil Pembelajaran Akuntansi - Sri Kuswati (AL -ALLAM, 2023)
Abstract: Lesson Study is an effort to improve learning processes and outcomes that are carried out collaboratively and continuously by a group of teachers. The main objectives of Lesson Study are to: (1) gain a better understanding of how students learn and teachers teach; (2) obtain certain results that are useful for other teachers in carrying out learning; (3) improve learning systematically through collaborative inquiry. (4) building a pedagogical knowledge, where a teacher can gain knowledge from other teachers. The benefits that Lesson Study can take include: (1) the teacher can document the progress of his work, (2) the teacher can get feedback from other members, and (3) the teacher can publish and disseminate the final results of Lesson Study. Lesson Study can be carried out through two types, namely school-based and MGMP-based. Lesson Study is carried out based on cyclic stages, which consist of: (1) planning (plan); (b) implementation (do); reflection (check); and follow-up (act). Keywords: lesson study, collaborative, plan, do, check, act.